Potential of wound healing in Bornean frog skin from genus hoplobatrachus and genus staurois - Doris, Anak Tang (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Since Hoplobatrachus of Indian origin is known to have healing potential, the genus that occurs in Borneo was used to further validate the finding. In addition, Genus Staurois that was known to be poisonous was also included in this study. This study will assess the healing process compared between non treated rat and normal dressing treated by using distilled water. The study was conducted on day 3, day 7 and day 14. Ruler measurement data and histology study were done for wound healing analysis. Three laboratory rats were used in this study. Ruler measurement and histological assessment data suggested that both H. rugolusus-treated and S. laptopalmatus-treated healed faster than S. guttatus-treated. Therefore, we suggest that probably H. rugolusus and S. laptopalmatus may have the potential in wound healing. Meanwhile, probably S. guttatus may not have the potential due to possibility to have toxicity skin of anuran. It would be an interesting topic for further study on wound healing properties of Bornean frog skin.